Enterocyte-Associated Microbiome of the Hadza Hunter-Gatherers - Turroni, Silvia; Rampelli, Simone; Centanni, Manuela; Schnorr, Stephanie L.; Consolandi, Clarissa; Severgnini, Marco; Peano, Clelia; Soverini, Matteo; Falconi, Mirella; Crittenden, Alyssa N.; Henry, Amanda G.; Brigidi, Patrizia; et al. (Frontiers in Microbiology, 2016)
By means of a recently developed non-invasive ex vivo minimal model based on the interaction of the human enterocyte-like HT29 cell line and fecal slurries, we explored the enterocyte-associated microbiome of 21 Hadza hunter-gatherers and 9 urban living Italians. Though reductionist, this model allows inferring the microbiota structural and functional arrangement as it interacts with enterocytes. Microbial suspensions obtained from Hadza or Italian stools were first evaluated for structural integrity by high resolution-scanning electron microscopy and co-incubated with HT29 cell monolayers. The enterocyte adherent microbiota fraction was then characterized by 16S rRNA gene sequencing and predictive functional profiling using PICRUSt. Compared to Italians, the Hadza enterocyte-associated microbiome was characterized by a greater amount of adhesive microorganisms with pathogenic potential, such as Proteobacteria, Erysipelotrichaceae, Enterococcus, Clostridium and Sarcina. These compositional characteristics were reflected in a functional enrichment in membrane transport, signal transduction, signaling molecules and interaction. Our results depict a new interesting mutualistic configuration of the enterocyte-associated microbiome in Hadza, stressing the importance of microbe-host interaction at the mucosal surface along the course of human evolution.